Microsoft Office Groove 2007 step by step - Jewell, Rick (Step by step, 2008)
A guide to Microsoft Office Groove covers such topics as creating collaborative workspaces, capturing and sharing data, setting up online discussion boards, sending instant messages and alerts, and publishing and synchronizing documents.